Perfluorooctanoic acid exposure impact a trade-off between self-maintenance and reproduction in lizards (Eremias argus) in a gender-dependent manner. (July 2020) - Zhang, Luyao; Meng, Zhiyuan; Chen, Li; Zhang, Guiting; Zhang, Wenjun; Tian, Zhongnan; Wang, Zikang; Yu, Simin; Zhou, Zhiqiang; Diao, Jinling
Abstract: The trade-off between self-maintenance and reproduction has been explored wildly in reptiles. However, the effects of exogenous pollutants on the life history traits of reptiles have not been paid attention to. In the current study, lizards ( Eremias argus ), living in the soil polluted by perfluorooctanoic acid (PFOA) were selected as the main focus. Bodyweight, survival rate, clutch characteristics and biochemical analysis (immune response, lipid accumulation, sex steroid secretion, antioxidant level, and metabolomics) were investigated and the results revealed that lizards' life-history trade-offs are gender-dependent: females were more inclined to choose a "Conservative" life-history strategy. After 60 days of exposure to PFOA, larger body weight, higher survival rate, stronger immune response, and lighter egg mass in females suggested that their trade-offs are more biased towards self-maintenance. Whereas, the "Risk" strategy would more popular among males: reduced body weight and survival rate, and suffering from oxidative damage indicated that males made little investment in self-maintenance. Graphical abstract: Image 1 Highlights: PFOA exposure induced trade-off between self-maintenance and reproduction in E. argus. This trade-off was gender specific in lizards. Females were inclined to choose a "Conservative" life-history strategy. The "Risk" strategy would more popular among males. Abstract : PFOA could induce a trade-off between lizard's self-maintenance and reproduction investment, and this trade-off was gender dependent.